Особливості вегетативного гомеостазу у вагітних з гестозом - Бенюк, В.О.; Майданник, І.В.; Диндар, О.А.; Ропотан, А.Г.; Королюк, Н.П.; Тимофеєва, О.В. (Таврический медико-биологический вестник, 2011)
Изучены особенности вегетативного гомеостаза на основе вариабельности сердечного ритма у беременных с физиологическим течением беременности и у беременных с гестозом. Проведено обследование 112 женщин, беременность которых осложнилась гестозом различной степени тяжести. Контрольная группа составила 20 небеременных женщин. Полученные данные позволят утверждать, что суточные параметры сердечного ритма отображают состояние регулятоных механизмов ВНС у беременных. Features of a vegetative homeostasis on the basis of variability of a cordial rhythm at pregnant women with physiological current of pregnancy and at pregnant women with gestosis are studied. Inspection of 112 women which pregnancy has become complicated gestosis a various degree of weight is lead. Control group has made 20 not pregnant women. Obtained data allow to approve, that daily parameters of a cordial rhythm display a condition controller mechanisms VNS at pregnant women.